EFFECT OF BROILER FINISHER PERFORMANCE IN COMMERCIAL RATIONS FERMENTED DUCKWEED BROILER FINISHERS (Saccharomyces cerevisiae) SUBSTITUTION - I G. W., Widiantara; Suarna, I W.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of fermented duckweed substitution in commercial rations on the performance of broilers. The research was conducted at Banjar Cabe, Darmasaba Village, Abiansemal District, Badung Regency, Bali for four weeks. This study used a completely randomized design (CRD) with four treatments, four replicates, and 16 experimental units, namely treatment P0 was given feed in the form of 100% BR2 commercial ration and treatments P1, P2, and P3 were given BR 2 commercial ration with yeast fermented duckweed substitution. bread each by 5%, 10%, and 15%. The variables observed were ration consumption, final body weight, body weight gain, and ration conversion (FCR). The results showed that ration consumption had no effect on all treatments. The variables of final body weight, body weight gain and ration conversion (FCR) had no effect on treatment P0, P1, and P2, but had an effect on P3. It can be concluded that substitution of baker's yeast fermented duckweed in commercial rations up to 5% and 10% did not decrease body weight gain, final body weight and FCR.